SISTEM INFORMASI GEOGRAFIS PEMETAAN TANGGUL KRITIS PADA SUNGAI BUNUT DI KECAMATAN RAWANG PANCA ARGA - Siregar, Hendriko; Muhammad Irwansyah; Amir Hamzah (Universitas Asahan, 2025)
Bunut River flows across Rawang Panca Arga District with its upstream in Setia Janji District, Asahan Regency and empties into balai River, Sei Balai District, Batubara Regency. The water discharge on the Bunut River causes flooding when the water discharge increases. Most flooding problems are caused by unstable and critical embankments. The aim of this research is to design a Geographic Information System and contain data regarding critical embankments in Rawang Panca Arga District. The location of critical embankments on the Bunut River can be mapped with a moteode using the ArcGis application version 10.3. Critical embankment problems on the Bunut River can be prevented with proper handling by strengthening the river banks with pairs of gabions. By strengthening river banks, it produces embankments that are safe from flood disasters when water discharge increases